PEMANFAATAN INTERNET UNTUK MEMPERBAHARUI MODEL PENGAJARAN DI PERGURUAN TINGGI - Herman Dwi Surjo lo Herman Dwi Surjo lo (LPMPP Universitas Negeri Yogyakarta, 1999)
The widespread acceptance of the inteniet and morespecifically the World Wide Web (WWW) has raised theawareness of educators to the potential for on-line educationand virtual university. The web as a new phenomenonin the info natiolnan dscape of the university is used tosupport course instruction. An innovatimodel of webbaseduniversity instruction is presented that more fullyexpresses and uses the power of the web in opening up [lieinteraction between student and knowledge.